US policy in Southwest Asia a failure in perspective - Lawrence, Robert Gilford 1923- (Nat. Defense Univ. Pr., 1984)
Over-reliance upon military action as the predominant instrument of US foreign policy in Southwest Asia is the danger against which this essay; warns. Colonel Robert G. Lawrence, is less troubled by questions of US military strength than by policymakers' insensitivity to the historical, religious, and regional dynamics of Southwest Asia in general and the Persian Gulf states in particular. Security assistance, although important, has been mistakenly considered the essential element of US policy when it should complement, not constitute US diplomacy. Too long, we have failed to understand the Arab view of the world in which they live. Our policymakers have slighted the complexity and the diversity of Arab religions, politics, and history-forces which inform and direct Arab actions. Colonel Lawrence directly addresses the tough questions, such as US support of Israel, widely inconsistent policies for foreign military sales, US failure in Iran, and US inaction during the Soviet invasion of Afghanistan. Interviewing over fifty prominent Arab government officials, military leaders, diplomats, scholars, and businessmen, Colonel Lawrence brings immediacy and insight to this frank, somewhat controversial study of Southwest Asia.
Keywords: Außenpolitik; Naher Osten; USA; Middle East -- Foreign relations -- United States; United States -- Foreign relations -- Middle East; Mittlerer Osten